Intra-Amniotic Infection with Ureaplasma parvum Causes Preterm Birth and Neonatal Mortality That Are Prevented by Treatment with Clarithromycin - Kenichiro Motomura (American Society for Microbiology, 2020)
ABSTRACT Intra-amniotic infection is strongly associated with adverse pregnancy and neonatal outcomes. Most intra-amniotic infections are due to Ureaplasma species; however, the pathogenic potency of these genital mycoplasmas to induce preterm birth is still controversial. Here, we first laid out a taxonomic characterization of Ureaplasma isolates from women with intra-amniotic infection, which revealed that Ureaplasma parvum is the most common bacterium found in this clinical condition. Next, using animal models, we provided a causal link between intra-amniotic inoculation with Ureaplasma species and preterm birth. Importantly, the intra-amniotic inoculation of Ureaplasma species induced high rates of mortality in both preterm and term neonates. The in vivo potency of U. parvum to induce preterm birth was not associated with known virulence factors. However, term-derived and preterm-derived U. parvum isolates were capable of inducing an intra-amniotic inflammatory response. Both U. parvum isolates invaded several fetal tissues, primarily the fetal lung, and caused fetal inflammatory response syndrome. This bacterium was also detected in the placenta, reproductive tissues, and most severely in the fetal membranes, inducing a local inflammatory response that was replicated in an in vitro model. Importantly, treatment with clarithromycin, a recently recommended yet not widely utilized antibiotic, prevented the adverse pregnancy and neonatal outcomes induced by U. parvum. These findings shed light on the maternal-fetal immunobiology of intra-amniotic infection. IMPORTANCE Preterm birth is the leading cause of neonatal morbidity and mortality worldwide. Multiple etiologies are associated with preterm birth; however, 25% of preterm infants are born to a mother with intra-amniotic infection, most commonly due to invasion of the amniotic cavity by Ureaplasma species. Much research has focused on establishing a link between Ureaplasma species and adverse pregnancy/neonatal outcomes; however, little is known about the taxonomy of and host response against Ureaplasma species. Here, we applied a multifaceted approach, including human samples, in vivo models, and in vitro manipulations, to study the maternal-fetal immunobiology of Ureaplasma infection during pregnancy. Furthermore, we investigated the use of clarithromycin as a treatment for this infection. Our research provides translational knowledge that bolsters scientific understanding of Ureaplasma species as a cause of adverse pregnancy/neonatal outcomes and gives strong evidence for the use of clarithromycin as the recommended treatment for women intra-amniotically infected with Ureaplasma species.